(untitled) (Delta Medical College Journal, 2015)
Background: Rape is one of the silent brutal sexual offences in Bangladesh. Despite strong laws against it, the evil of rape continues to rise. Increasing trend of the silent cruel sexual offence (rape) represents a major psychopath sexual disorder and public health problem and progress of the country. Objective: The aim of the study was to determine the pattern of alleged rape victims in a rural district of Bangladesh with the ultimate aim to create public awareness about the brutal crime. Materials and method: This retrospective study was carried out on 330 sexually assailed alleged rape victims report forms, who reported at Faridpur Medical College, Bangladesh from 2007 to 2011 for medical examination. Results: Among the study subjects maximum number (70.0%) of alleged rape cases were under the age of 20 years. More than two-thirds (64.60%) of the assailants were known to the victims, most of the incidents (64.20%) occurred in the victims houses and nearby places. The study also revealed that minimum number of victims (14.20%) reported within 24 hours for medical examination. Almost one fourth of the alleged rape cases were gang rape and no positive finding in favour of sexual intercourse was found in about three fourth (72.40%) of cases. Conclusion: Public awareness about rape would be effective to report in due time with preserving the evidence of crime and modern techniques like DNA diagnosis may be of help to detect the assailant. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22237 Delta Med Col J. Jan 2015; 3(1): 31-35